2022
DOI: 10.1186/s13071-022-05348-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening and phylogenetic characterization of tick-borne pathogens in a population of dogs and associated ticks in Egypt

Abstract: Background The incidence or recurrence of tick-borne diseases (TBDs) in animals and humans is increasing rapidly worldwide, but there is insufficient information about TBDs infecting dogs in Egypt. Thus, the present study was conducted to screen and genetically identify tick-borne pathogens (TBPs) in dogs and associated ticks by microscopic examination and polymerase chain reaction (PCR). Methods In Cairo and Giza governorates, 208 blood samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…scupense. To the best of our knowledge, the detection of A. marginale in R. sanguineus is exceptionally rare [46], and this pathogen has not been detected in Hy. scupense.…”
Section: Discussionmentioning
confidence: 96%
“…scupense. To the best of our knowledge, the detection of A. marginale in R. sanguineus is exceptionally rare [46], and this pathogen has not been detected in Hy. scupense.…”
Section: Discussionmentioning
confidence: 96%
“…Since the sampled animals were asymptomatic, the positive dogs were probably in the chronic phase of infection. Although the prevalence was lower than those obtained in other African studies [ 11 , 40 , 42 , 45 , 56 ], the detection of this pathogen deserves attention not only because of the disease’s consequences for dogs’ health, but also because of the occasional reports of E. canis acting as a zoonotic agent [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 76%
“…In Africa some studies showed A. phagocytophilum in Rhipicephalus sanguineus , Haemophysalis elliptica and Hyalomma spp. [ 8 , 18 , 45 , 46 ]. In the dog population under this study, ticks belonging to the genus Rhiphicephalus and Haemophysalis were found, with the species R. sanguineus and H. leachi (unpublished data) highly represented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following supporting information can be downloaded at: , Table S1: PRISMA checklist and additional checklist based on Migliavaca et al, 2020, guidelines; Table S2: List of papers excluded during full-text examination and relevant exclusion criteria; Table S3: Details of qualitative analysis; Table S4: Details of critical appraisal. References [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ,…”
mentioning
confidence: 99%